Faktor-Faktor Yang Mempengaruhi Harga Saham Perusahaan Sub Sektor Property dan Real Estate - Delala Yuvita Sari; Riana Rahmawati Dewi; Rosa Nikmatul Fajri (Universitas Batanghari Jambi, 2020)
This study aims to analyze the effect of return on assets (ROA), return on equity (ROE), earnings per share (EPS), current ratio (CR), debt to equity ratio (DER) on stock prices. The sampling technique uses purposive sampling. Based on purposive sampling, 34 samples of property and real estate companies listed on the Indonesia Stock Exchange for the period of 2016-2018 were obtained in accordance with predetermined criteria, so that the total sample of 102 total were ready to be processed. The data analysis method used in this study is multiple linear regression analysis. The results of this study prove that earnings per share variable has a positive and significant effect on stock prices. Conversely the current ratio variable has a negative and significant effect on stock prices, while the variable return on assets, return on equity, debt to equity ratio has no effect on stock prices.